2012
DOI: 10.1002/cne.23230
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the subnuclei in rat habenula

Abstract: The mammalian habenula is involved in regulating the activities of serotonergic and dopaminergic neurons. It consists of the medial and lateral habenulae, with each subregion having distinct neural connectivity. Despite the functional significance, manipulating neural activity in a subset of habenular pathways remains difficult because of the poor availability of molecular markers that delineate the subnuclear structures. Thus, we examined the molecular nature of neurons in the habenular subnuclei by analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
109
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(132 citation statements)
references
References 0 publications
16
109
0
4
Order By: Relevance
“…2 A and Dataset S1, the TRAP samples show robust enrichment of known markers of MHb neurons, including Chrna3, Chrnb4, Tac2, and Gpr151, in agreement with other studies (14,17), whereas nonneuronal transcripts (e.g., glial genes) are depleted (red in Fig. 2A).…”
Section: Trap Analysis Of Cholinergic Mhb Neurons Reveals Enrichment Ofsupporting
confidence: 89%
See 1 more Smart Citation
“…2 A and Dataset S1, the TRAP samples show robust enrichment of known markers of MHb neurons, including Chrna3, Chrnb4, Tac2, and Gpr151, in agreement with other studies (14,17), whereas nonneuronal transcripts (e.g., glial genes) are depleted (red in Fig. 2A).…”
Section: Trap Analysis Of Cholinergic Mhb Neurons Reveals Enrichment Ofsupporting
confidence: 89%
“…A number of studies have begun to dissect the medial and lateral habenular nuclei in an effort to determine whether subpopulation differences in cytoarchitecture and connectivity could be correlated to molecular markers and electrophysiological properties (14)(15)(16)(17). For instance, the dorsal and ventral parts of the MHb can be clearly divided based on their respective enrichment in the neuropeptide Tachykinin 1, also known as substance P (SP), or the ACh synthesizing enzyme choline acetyltransferase (ChAT), and the segregation of their efferents to different parts of the IPN (18).…”
mentioning
confidence: 99%
“…Although we selectively modulate cholinergic neurons of the MHb, this cell population has been previously shown to release glutamate and/or acetylcholine (Qin & Luo 2009;Ren et al 2011;Aizawa et al 2012). Therefore, it remains unclear which neurotransmitter system is responsible for driving the reinstatement phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the MHb may play a larger role in adaptive behaviors, where mounting evidence has demonstrated that loss of vMHb function leads to deficits in fear extinction and escape behaviors. Nevertheless, while the circuitry and cellular composition of the MHb has been well-characterized, the endogenous functions of the MHb remain relatively unknown and have recently become the focus of addiction neuroscience (Qin & Luo 2009;Aizawa et al 2012;Lima et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although both receptors are activated by either ligand, SP preferentially activates NK1 receptors and NKB preferentially activates NK3 receptors. In contrast to the expression of NKB, which is extremely dense and ubiquitous throughout the MHb (Lucas et al, 1992;Marksteiner et al, 1992;Lein et al, 2007), strong SP expression is confined to the dorsal one-third of the MHb (Lein et al, 2007;Aizawa et al, 2012). Both NK1 and NK3 receptors are strongly expressed in the cholinoceptive/cholinergic ventral two-thirds of the MHb (Langlois et al, 2001;Lein et al, 2007;Commons and Serock, 2009).…”
Section: Neuroadaptation During Chronic Nicotine Exposurementioning
confidence: 99%